Preliminary report on Trypanosoma cruzi presence in Peruvian North and Northeast departments - Solís, Hilda (2012)
Objectives: To perform an epidemiological study on presence of Chaga’s disease and its vectors at northern and nor oriental Peru. Design: Descriptive, transversal study. Setting: Daniel A. Carrion Tropical Medicine Institute, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Triatomines positive to Trypanosoma cruzi Chagas 1909; one month-old Swiss- Webster male rats. Interventions: In September 2008 a visit was done to Chilete, Paredones, Contumaza province, Cajamarca, and to Pampa Larca, La Puerta, Guitarras and Suyo at Ayabaca province, Piura, collecting 10 Panstrongylus chinai (Del Ponte, 1929) specimens at Piura and 12 Panstrongylus herreri (Wygodzinsky, 1948) specimens at Chilete, Cajamarca. Trypanosoma strains were isolated in Swiss Webster white male one month-old rats, and maintained by successive transfers. Both parasitemia curve and morphometric study of blood tripomastigotes were done. Infected rats were sacrificed at 30 days from inoculation, viscera were separated and pathology study was performed. Fifty-nine blood samples were obtained from inhabitants’ finger pulp in paper filter to look for IgG anti-T. cruzi antibodies by ELISA and indirect immunofluorescence (IIF). Main outcome measures: Identification of triatomines and infection by Trypanosoma cruzi; presence of IgG anti- T. cruzi antibodies in inhabitants. Results: Two P. chinai and one P. herreri specimens were positive for Trypanosoma cruzi in the triatomines collected. Maximum peak of parasitemia curve occurred at 20 days. T. cruzi amastigotes nests were found in rat myocardium and skeletal muscle. Ten inhabitant’s blood samples (16,9%) were reactive to IgG anti-T. cruzi antibodies, with concordant results for both techniques. Conclusions: Presence of the parasite in vectors and of antibodies in humans confirmed that in Peruvian northern and nor oriental settings there exists active T. cruzi infection with all epidemiological chain links present to develop the disease.